2011
DOI: 10.1038/nutd.2011.10
|View full text |Cite
|
Sign up to set email alerts
|

Microfibrillar-associated protein 5 is linked with markers of obesity-related extracellular matrix remodeling and inflammation

Abstract: Objective:Microfibrillar-associated protein 5 (MFAP5) is an extracellular matrix (ECM) glycoprotein, which is colocalized with microfibrils in elastin networks. Its function in adipose tissue (AT) is not known. We have recently shown that the expression of MFAP5 is downregulated in AT along with weight reduction (WR) in persons with metabolic syndrome (MetS). The aim of this work was to study whether the change of MFAP5 mRNA expression in response to WR is associated with markers of adiposity, glucose metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…In samples of subcutaneous abdominal adipose tissue, leptin (LEP) expression was reported in six studies . In studies of diet only or in the diet‐only arm of combined dietary + exercise change, all studies reported a decrease in LEP expression with weight loss ( n = 4) with a statistically significant decrease reported in two studies . However, a decrease in expression was also noted in the energy surplus intervention in both study arms .…”
Section: Resultsmentioning
confidence: 99%
“…In samples of subcutaneous abdominal adipose tissue, leptin (LEP) expression was reported in six studies . In studies of diet only or in the diet‐only arm of combined dietary + exercise change, all studies reported a decrease in LEP expression with weight loss ( n = 4) with a statistically significant decrease reported in two studies . However, a decrease in expression was also noted in the energy surplus intervention in both study arms .…”
Section: Resultsmentioning
confidence: 99%
“…The design of the Gene Expression in Obesity and Insulin Resistance (GENOBIN) study has been reported earlier (2,3). Altogether, 46 overweight or obese (BMI 28–40 kg/m 2 ) subjects 40–70 years of age were randomly assigned to one of two groups: a weight-reduction group ( n = 28) or a weight-maintenance control group ( n = 18) (2).…”
Section: Methodsmentioning
confidence: 99%
“…In searching new putative genes related to obesity and type 2 diabetes, we have previously demonstrated a multitude of changes in adipose tissue (AT) gene expression in response to weight reduction in individuals with metabolic syndrome (2,3). Among the downregulated genes was calcineurin-like phosphoesterase domain containing 1 ( CPPED1 ) (2); its function in AT is completely unknown.…”
mentioning
confidence: 99%
“…They demonstrated that weakening of the adipose tissue ECM by genetic disruption of collagen VI resulted in considerable improvement of the metabolic phenotype in the context of a high-fat diet and in mice with the ob/ob mutation. In addition, a study by Vaittinen et al (11) showed that the microfibrillarassociated protein 5 (MFAP5) is highly expressed in human adipose tissue and is correlated with markers of insulin resistance, suggesting that MFAP5 is related to ECM remodeling during the development of obesity. Kolehmainen et al (12) recently studied the effect of weight loss on gene expression in the adipose tissue of obese individuals with impaired metabolic function and found that genes regulating the ECM and cell death showed a strong downregulation after long-term weight reduction.…”
mentioning
confidence: 99%